O humor em mídia digital como aporte ao salto existencial kierkegaardiano e ao despertar benjaminiano: teoria e estudo de caso - Silva, Gilmar Pereira da (2014)
By means of a sincronic and diacronic approach, the present study attempts to analize humor as an interpretation of reality attentive to its finite character, by way of humoristic images, and more specifically, in those images circumscribed by the space of the web. For this, the investigation was centered in a bibliographic revision and in the analysis of the humoristic blog Kibe Loco. Taking as principal theoretical references Søren Aabye Kierkagaard and Walter Benjamin, the notion of humor was studied as a way of signifying reality that which would favor an existencial leap, according to the first author and as a dialectical image as a historical category that would provoke a waking up according to the second in order to observe the function of humoristic images in digital medias. In this way, it was sought to comprehend the extent to which dialectical images would contribute to the referred leap and waking up , qualitative changes in the relation of the individual with herself and with society as a whole, always making the comparison with the diverse humoristic production of the blog. The first chapter is centered on humor; the second on the image, above all humoristic images; the third chapter combines the theories of the first two with the hypertextual writing of digital platforms